The Programmed Cell Death of Macrophages, Endothelial Cells, and Tubular Epithelial Cells in Sepsis-AKI - Li, Chao; Wang, Wei; Xie, Shuai-shuai; Ma, Wen-xian; Fan, Qian-wen; Chen, Ying; He, Yuan; Wang, Jia-nan; Yang, Qin; Li, Hai-di; Jin, Juan; Liu, Ming-ming; et al. (Frontiers in Medicine, 2021)
Sepsis is a systemic inflammatory response syndrome caused by infection, following with acute injury to multiple organs. Sepsis-induced acute kidney injury (AKI) is currently recognized as one of the most severe complications related to sepsis. The pathophysiology of sepsis-AKI involves multiple cell types, including macrophages, vascular endothelial cells (ECs) and renal tubular epithelial cells (TECs), etc. More significantly, programmed cell death including apoptosis, necroptosis and pyroptosis could be triggered by sepsis in these types of cells, which enhances AKI progress. Moreover, the cross-talk and connections between these cells and cell death are critical for better understanding the pathophysiological basis of sepsis-AKI. Mitochondria dysfunction and oxidative stress are traditionally considered as the leading triggers of programmed cell death. Recent findings also highlight that autophagy, mitochondria quality control and epigenetic modification, which interact with programmed cell death, participate in the damage process in sepsis-AKI. The insightful understanding of the programmed cell death in sepsis-AKI could facilitate the development of effective treatment, as well as preventive methods.